2019
DOI: 10.1177/1757913919892026
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and readmission of patients with cardiovascular disease in South Korea

Abstract: Aims: The purpose of this study was to investigate the health-related quality of life (HRQOL) of patients with cardiovascular disease and its relationship to hospital readmission. Methods: The cross-sectional study used data from 1037 adults aged ⩾19 years diagnosed with myocardial infarction or angina pectoris. Raw data were obtained from the fourth to sixth Korea National Health and Nutrition Examination Survey (2007–2014). Results: Readmission was found to be associated with age, living status, education le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Therefore, the prediction of readmission for acute care suggests that the attention to clinical findings would be considered in long-term care than in acute care settings. Similar to other reports on CVD-related 30-day readmission rates among Medicare beneficiaries, this study found higher 30-day readmission rates among men, patients aged < 65 years, those from lower-income households, and those with multiple comorbidities ( 12 , 18 20 , 26 , 27 , 30 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the prediction of readmission for acute care suggests that the attention to clinical findings would be considered in long-term care than in acute care settings. Similar to other reports on CVD-related 30-day readmission rates among Medicare beneficiaries, this study found higher 30-day readmission rates among men, patients aged < 65 years, those from lower-income households, and those with multiple comorbidities ( 12 , 18 20 , 26 , 27 , 30 ).…”
Section: Discussionsupporting
confidence: 89%
“…Risk prediction of 30-day readmission for patients with AMI could be analyzed through a variety of assessment tools ranging from patient interviews to screening methods, by using a different set of variables (26)(27)(28). Several studies have investigated the predictors, viz., demographic characteristics, admission and discharge predictors, major surgery, comorbidities, length of stay, medications, and special procedures that are associated with 30-day readmissions (29,30). One of the first steps in reducing 30-day readmissions is understanding and determining the key causes that lead to instances of readmission and developing a predictive model to assess the risk of readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found higher 30-day readmission rates among men, those aged 65 years and older, patients from lower-income households, Medicare beneficiaries, and those who had multiple comorbidities, and similar results were reported on CVD-related 30-day readmission rates [12,[18][19][20]26,27,30]. We also found that patients who were discharged for other reasons, such as those discharged against medical advice or voluntarily discharged, were more likely to have 30-day readmissions compared to those who had a normal discharge.…”
Section: Discussionsupporting
confidence: 88%
“…Risk prediction of 30-day readmission for patients with AMI could be accomplished with a variety of assessment tools ranging from multidisciplinary patient interviews to simple screening tools using a handful of variables [ 26 , 27 , 28 ]. Several studies have investigated predictors: demographic characteristics, admission and discharge types, comorbidities, length of stay, medications and special procedures associated with 30-day readmissions [ 29 , 30 ]. However, healthcare professionals still struggle to predict those patients who are at high risk of hospital readmission.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study contrast with a previous study, where a low QOL predicted readmission. Indeed, QOL is recognised as a significant predictor of readmission for CAD patients (Dhital et al, 2018;Heo et al, 2009;O'Loughlin et al, 2010), where CAD patients who experience physical and emotional symptoms that result in a poor QOL are linked to a higher frequency of readmission (Kim et al, 2019;Sethares and Elliott, 2004;O'Loughlin et al, 2010). Likewise, CAD was found to be a chronic condition with an unstable course and unpredictable exacerbations and progression of symptoms, which resulted in a poor QOL and was linked to an increased frequency of readmission (Kim et al, 2019;Sethares and Elliott, 2004;O'Loughlin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%